LEARNING ASSISTANCE AND CURRICULUM ASSESSMENTS IN THE VOCATIONAL HIGH SCHOOL IMPLEMENTER PROGRAM OF THE VOCATIONAL HIGH SCHOOL CENTRE OF EXCELLENCE (SMK PK) - I Made Indra P.; Fanny Novika; Holil Padli; C. Nike Septivani; John Jhony Kurniawan (Yayasan Education and Social Center, 2022)
The Center for Excellence Vocational School Assistance Program is a vocational development program with certain expertise and competencies in improving quality and performance. This activity is strengthened through partnerships and alignment with the business world, industry, and world of work, which eventually becomes a vocational reference school that can function as a driving school and a center for quality improvement. And other SMK performance. This Community Service activity provides learning assistance and assessment at the Vocational High School, implementing the Center of Excellence program implemented at SMKN 11 Bandung and SMK Wahidin Cirebon. It can conclude that the mentoring results from August 2021 to December 2021 obtained 100% achievement results with the implementation of a learning mentoring program with the new paradigm of the Vocational High School of Excellence, which carry online and offline operational curriculum assistance